БОЛАЛАР ФАРОВОНЛИГИНИНГ ТАЪМИНЛАНИШИГА ЭРИШИШНИНГ ПЕДАГОГИК ЙЎНАЛИШИ - Қадрекова, А.Қ. (SCIENCE and SOCIETY, 2018)
The article focuses on the issues of creating well-being of children in the family, the participation of teachers, parents and mahalla in the solution of these problems, and educational role of the environment.